Impact of the metabolic syndrome on peripheral nerve structure and function in type 2 diabetes. (21st March 2021) - Issar, Tushar; Tummanapalli, Shyam S.; Borire, Adeniyi A.; Kwai, Natalie C. G.; Poynten, Ann M.; Arnold, Ria; Markoulli, Maria; Krishnan, Arun V.
Abstract: Background and purpose: There is a strong association between the metabolic syndrome in diabetes and the development of peripheral neuropathy; however, the pathophysiological mechanisms remain unknown. Methods: Participants with type 2 diabetes and metabolic syndrome (T2DM/MetS, n  = 89) and type 2 diabetes alone (T2DM; n  = 59) underwent median nerve ultrasound and excitability studies to assess peripheral nerve structure and function. A subset of T2DM/MetS ( n  = 24) and T2DM ( n  = 22) participants underwent confocal microscopy to assess central and inferior whorl corneal nerve structure. Neuropathy severity was assessed using the modified Toronto Clinical Neuropathy Score (mTCNS). Diabetes groups were similar for age, sex distribution, diabetes duration, hemoglobin A1c, insulin treatment, and renal function. Sixty healthy controls similar for age and sex distribution were recruited for comparison. Results: Participants with T2DM/MetS manifested with a greater mTCNS compared to T2DM ( p  < 0.05). Median nerve cross‐sectional area was larger in the T2DM/MetS group compared to the T2DM cohort ( p  < 0.05). Participants with T2DM/MetS had reductions in central (all p  < 0.01) and inferior whorl (all p  < 0.05) nerve measures. Compared to T2DM, the T2DM/MetS group demonstrated more severe changes in nerve excitability measures, which was due to reduced sodium channel permeability and sodium–potassium pump function. In comparison, only sodium channel permeability was reduced in the T2DM group. Conclusions: Compared to participants with type 2 diabetes alone, those with diabetes and metabolic syndrome manifested greater alterations in peripheral nerve structure and function, which may be due to reduced function of the sodium–potassium pump. Abstract : Participants with type 2 diabetes and metabolic syndrome demonstrated more severe changes in nerve excitability measures, which was due to a reduction in sodium channel permeability and sodium–potassium pump function. In contrast, in subjects with type 2 diabetes alone, only sodium channel permeability was decreased. A larger median nerve cross‐sectional area and a greater reduction in corneal confocal microscopy metrics were observed in participants with type 2 diabetes and metabolic syndrome.